Study on the Importance of Employee Performance Assessment and Lost Productive Time Rate Determination in Garment Assembly Lines - KAYAR, MAHMUT (INST CHEMICAL FIBRES, 2017)
This study primarily includes theoretical information on the performance and lost productive time of a firm. Furthermore t-shirt sewing operations of a garment firm were analysed and time measurement for each operation was carried out by the time keeping method. By considering the measurements obtained, different performance estimations, the firm's lost productive time rates, and the standard time was calculated within 5 different scenarios. According to each sewing standard time obtained, the assembly line balancing practice was carried out using the Hoffman method. Later on results of the assembly line balancing were compared, and the importance of employee performance assessment and its lost productive time rates for firms were discussed. The aim of the study was to emphasize the value of impeccable determination of the employee performance assessment and lost productive time rates. Consequently garment firms will be more cautious in calculating the standard time and will be able to reach their production target within the accurate measurement they obtain.
Keywords: employee performance; lost productive time; standard time; assembly line balancing; ready-made clothing; hoffman method; BALANCING PROBLEM